1994
DOI: 10.1007/bf02348223
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural study of nonfunctioning adrenocortical adenoma

Abstract: Abstract. Nonfunctioning adrenocortical adenomas obtained from 40 and 60-year-old males were examined by electron microscopy. Light microscopically, the tumors were shown to consist of clear cells and compact cells in both cases. However, compact cells predominated in the former case, and clear cells in the latter. Electron microscopy revealed that most of the cells in the former case had abundant organelles, including well-developed, smooth and rough endoplasmic reticulum, Golgi apparatus, and mitochondria wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…6 With respect to ultrastructural features of nonfunctioning adrenocortical adenomas, we have already reported that organelles including mitochondria, smooth endoplasmic reticulum (SER) and rough endoplasmic reticulum (RER) were not developed compared to those in functioning adenomas. 7,8 To our knowledge, the precise ultrastructural characteristics in adenomas from preclinical Cushing's syndrome are unknown. We studied two adenomas from preclinical Cushing's syndrome and have attempted to clarify their ultrastructural features and compare them with adenomas from overt Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…6 With respect to ultrastructural features of nonfunctioning adrenocortical adenomas, we have already reported that organelles including mitochondria, smooth endoplasmic reticulum (SER) and rough endoplasmic reticulum (RER) were not developed compared to those in functioning adenomas. 7,8 To our knowledge, the precise ultrastructural characteristics in adenomas from preclinical Cushing's syndrome are unknown. We studied two adenomas from preclinical Cushing's syndrome and have attempted to clarify their ultrastructural features and compare them with adenomas from overt Cushing's syndrome.…”
Section: Introductionmentioning
confidence: 99%